Book reviews.
The Psychology Research Handbook : A Guide for Graduate Students and Research Assistants, by Frederick T. L. Leong and James T. Austin, eds. Reviewed by George Hayward
E-Quality : Bridging the Total Quality Involvement Gap, by Gillian Shapiro, Paul Levy and Swasti Mitter. Reviewed by Dave Hall.